The role of the hematocrit on the radial dispersion of red blood cells in glass capillaries - Lima, R. (2010)
The flow properties of blood in the microcirculation depend strongly on the hematocrit (Hct), microvessel geometry, and cell properties. Previous in vitro studies have measured the radial displacement of red blood cells (RBCs) at concentrated suspensions using conventional microscopes. However, they have used transparent suspensions of ghost red cells, which may have different physical properties than normal RBCs. In this study, we have used a new approach (confocal micro-PTV) to obtain direct and quantitative detailed descriptions of the flow behaviour of RBCs in concentrated suspensions of normal RBCs. The experiments were performed in 100 mm glass capillaries at Reynolds numbers (Re) of 0.005 and Hcts from 3 to 35%. Emphasis was devoted to the radial dispersion of RBCs located in the middle plane.